Letter to Jane Tolmach from Ben F. Ruffner - Ben F. Ruffner:::::: (1966)
A letter from Ventura County Superior Court Judge Ben F. Ruffner congratulates Jane Tolmach on her recent election. He remarks that her achievement recalls the time when "Goldie" held the same position. Ruffner expresses warm regards and says he looks forward to hearing about developments in her new role.